Academic Resilience and Growth Mindset of Senior High School Students in Relation to Their Early Learning Experiences - Mega Aria Monica; Sunyono Sunyono; Mujiyati; Hasan Hariri; Rabiyatul Adawiyah (Women, Education, and Social Welfare, 2026)
This study aims to examine senior high school students' early learning experiences, growth mindset, and academic resilience to provide baseline data for developing digital guidance services. A quantitative descriptive design was used, involving an online survey with 3,746 students. The survey included both open-ended questions to explore early learning experiences and closed-ended Likert scale questions to assess growth mindset and academic resilience. Data analysis revealed that 66.20% of students reported mixed early learning experiences, 30.25% reported positive experiences, and 3.55% reported less positive experiences. Regarding growth mindset and academic resilience, 77.95% and 83.08% of students, respectively, were categorized at moderate levels. The results indicate that while students exhibit adaptive potential, their growth mindset and coping strategies are still developing. These findings highlight the importance of understanding the factors influencing students' mindset and resilience. This study suggests the need for reflective e-guidance services to help students strengthen their growth-oriented beliefs and improve their academic resilience, providing a promising approach to supporting students' learning and development.